2016
DOI: 10.1080/10810730.2015.1064494
|View full text |Cite
|
Sign up to set email alerts
|

Identification With Characters, Elaboration, and Counterarguing in Entertainment-Education Interventions Through Audiovisual Fiction

Abstract: The aim of this article is to further knowledge of the explanatory processes of narrative persuasion in the field of health communication, using data obtained in a research study of entertainment-education based on audiovisual fiction. Participating in the study were 208 young persons between the ages of 14 and 20, randomly distributed to three different groups. Each of the groups was exposed to a different episode of the Colombian television series Revelados, desde todas las posiciones. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 27 publications
3
49
0
14
Order By: Relevance
“…This study also makes a significant contribution to research into narrative persuasion and the role of emotions and identification with characters as explanatory mechanisms (de Graaf, 2014;de Graaf et al, 2012;Hoeken & Fikkers, 2014;Hoeken et al, 2016;Hoeken & Sinkeldam, 2014;Igartua & Barrios, 2012;Igartua & Vega, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This study also makes a significant contribution to research into narrative persuasion and the role of emotions and identification with characters as explanatory mechanisms (de Graaf, 2014;de Graaf et al, 2012;Hoeken & Fikkers, 2014;Hoeken et al, 2016;Hoeken & Sinkeldam, 2014;Igartua & Barrios, 2012;Igartua & Vega, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…In the field of narrative persuasion, it has been shown that identification with characters plays an important mediating role: For a narrative to cause a persuasive impact there must be a high identification with the characters involved (de Graaf et al, 2012;Hoeken & Fikkers, 2014;Igartua & Barrios, 2012;Igartua & Vega, 2016). In this context, identification with characters is a cognitive-affective process that takes place during reception (reading, viewing) of the narrative message, and that is linked to perspective-taking or cognitive empathy (putting oneself in the shoes of the character), emotional empathy (feeling the same emotions as the character), and the temporary loss of self-awareness (the receiver of the narrative imagines being the character, taking on his or her identity, and becoming merged with the character) (Cohen, 2001;Igartua & Barrios, 2012;Moyer-Gusé, 2008).…”
Section: Similarity Identification With Characters and Persuasive Imentioning
confidence: 99%
See 2 more Smart Citations
“…Ello no solo ha supuesto un avance teórico en el conocimiento de los procesos de persuasión narrativa, sino que ha dado lugar a la aplicación de dicho conocimiento para diseñar intervenciones cuya meta final es tratar de resolver problemas sociales (Cohen, Tal-Or, & Mazor-Tregerman, 2015;Igartua & Frutos, 2017;Wojcieszak, Azrout, Boomgaarden, Alencar, & Sheets, 2017;Wojcieszak & Kim, 2016) y/o mejorar la salud de las personas (Igartua & Vega, 2016;Moyer-Gusé, Chung, & Jain, 2011;Murphy, Frank, Chatterjee, & Baezconde-Garbanati, 2013). Un segundo avance teórico que cabe resaltar es el desarrollo de modelos teóricos sobre los mecanismos o procesos que explican cómo se produce la influencia de los mensajes narrativos en las personas (Green & Brock, 2000;MoyerGusé, 2008;Slater & Rouner, 2002).…”
Section: Introductionunclassified